Biologi Lalat Sciarid, Bradysia ocellaris (Diptera : Sciaridae), Serangga Hama pada Pertanaman Jamur Tiram - Rostaman Rostaman; Agus Dana Permana; Tati S. Subahar; Soelaksono Sastrodihardjo (Universitas Gadjah Mada, 2007)
Bradysia ocellaris Comstock is an important insect pest of oyster mushroom at Bandung. Eggs are oval, 0.44 ± 0.12 mm in length, 0.26 ± 0.08 mm in width, and translucent. Larvae are worm-like, legless, translucent, and capsule distinctive black. Larvae consist four instars. Pupae are obtectate, 2040 ± 0.22 mm in length, and 0.69 ± 0.10 mm in width. Adults are small, females 2.58 ± 0.28 mm and males 2021 ± 0.28 mm in length. Life cycle is 16 -6 26 days. Larvae feed on media, mycelia and fruit bodies.